The Role of Education in Rural Communities (LEARNing Landscapes, 2010)
Drawing upon a conversation held in rural Prince Edward Island, in this article I explore community questions regarding the role of education in Canada. I present five brief vignettes and then consider these through a lens that recognizes the criticality of community, context, and culture.
Keywords: community; education; canada; context; culture; rural